The Patient Satisfaction Scale: Validation of a Portuguese Version in Women Receiving Obstetric Care - Sim-Sim, Maria Margarida (2015)
Satisfaction of the obstetric patient is an indicator taken in account in health reports. Previous studies point towards several dimensions. In order to better evaluate health care services, it is curtail to have Portuguese language tools of easy appliance. The aim of the study is to validate the PSS in Portuguese. This is a descriptive study using a convenience sample of ninety one mothers. Participants were primary healthcare clients with children aged of 1 or less. The analysis regarded sensitivity, reliability, as well as concurrent, discriminant, converging and factorial validity. After Promax rotation, three factors were extracted explaining 82.13% of the variance. Reliability analysis was observed by split-half method showing a Spearman-Brown correlation coefficient of 0.91. Cronbach’s alpha of the Portuguese PSS total scale and subscales were satisfactory with coefficients between 0.829 and 0.941. Concurrent validity was supported by a continuous variable of support from nurses. Discriminant validity showed in women with a normal vaginal delivery, a higher satisfaction both globally and on the three dimensions. The properties observed at the PSS have shown to be satisfactory. PSS reveals itself as a valid measure of the obstetric client’s satisfaction.